1983
DOI: 10.1055/s-2007-969871
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alkaloid Formation and Storage in Cell Suspension Cultures of Catharanthus roseus

Abstract: The localization and storage of alkaloids were investigated in a low producing cell suspension culture of CATHARANTHUS ROSEUS(L.) G. Don. (Apocynaceae). Fluorescence microscopy and electron microscopy indicate alkaloid accumulation to occur inside the vacuoles of particular cells. These alkaloid storage cells exhibit a vacuolar pH of 3, while "normal" cells of a suspension culture have a vacuolar pH of about 5. Alkaloids are taken up in their unprotonated forms, trapped by protonation inside the vacuole and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…Furthermore malonate reduces malate uptake (17) (6). Some cases of definitive sequestration have been described in which the compounds undergo conformational changes (25) or ion-trap mechanism (22). However, MACC is not capable of symetry changes and therefore trapping cannot result from conformational changes of the transported substance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore malonate reduces malate uptake (17) (6). Some cases of definitive sequestration have been described in which the compounds undergo conformational changes (25) or ion-trap mechanism (22). However, MACC is not capable of symetry changes and therefore trapping cannot result from conformational changes of the transported substance.…”
Section: Discussionmentioning
confidence: 99%
“…1); therefore, their cellular accumulation mechanisms may be particularly important for the final levels of the anticancer TIAs. In C. roseus, TIAs have been shown to accumulate in the vacuoles by histochemical and cytological techniques (Yoder and Mahlberg, 1976;Neumann et al, 1983), the TIA serpentine was shown to accumulate mostly in the vacuoles of cell cultures (Deus- Neumann and Zenk, 1984), and immunocytochemical localization of vindoline indicated its major presence in the central vacuole and in small vesicles of mesophyll cells (Brisson et al, 1992). However, a thorough characterization of the subcellular accumulation of TIAs in the leaves of C. roseus, the only organ where the anticancer TIAs are accumulated, has not been performed.…”
Section: Conditionmentioning
confidence: 99%
“…Early work suggested that vacuolar accumulation of TIAs and other alkaloids was mediated either by highly specific carriers (Deus- Neumann andZenk, 1984, 1986;Wink, 1993) or by an unspecific ion-trap mechanism in which the alkaloids, being weak bases, accumulate by diffusion in the acidic vacuole (Guern et al, 1987;Renaudin, 1989;Blom et al, 1991;Wink, 1993). However, recent work on alkaloid transmembrane transport has consistently supported the H + /alkaloid antiport mechanism for the alkaloids berberine in Coptis japonica and nicotine in tobacco (Nicotiana tabacum; Otani et al, 2005;Morita et al, 2009;Shoji et al, 2009).…”
mentioning
confidence: 99%
“…The alkaloid ancistroheynine A was found in the tip of the shoot and leaf midrib of Liana Ancistrocladus heyneanus and ancistrocladine was found in the branch root of the plant by FT-Raman investigations (Urlaub et al 1997). Many more articles are published describing the localization of different alkaloids with different techniques (Verzár -Petri 1975;Yoder and Mahlberg 1976;Furr and Mahlberg 1981;Neumann et al 1983;Platt and Thomson 1992;Bringmann et al 1996;Mösli Waldhauser and Baumann 1996;Meininger et al 1997;Cai et al 1999;Corsi and Bottega 1999;Bottega et al 2004;Pasqua et al 2004;Alcantara et al 2005;Frosch et al 2006Frosch et al , 2007aNikolakaki and Christodoulakis 2006;Mesjasz -Przybyiowicz et al 2007;Liang et al 2009;Moraes et al 2009;Argyropoulou et al 2010;Christodoulakis et al 2010). …”
Section: Introductionmentioning
confidence: 99%